Comparison of different types of reasoning & proof present in solved tasks from geometry in Slovak and Czech mathematics textbooks for lower secondary school - Novotná, Jarmila; Kozánek Kiss, Tünde; Michal, Jakub; Vankúš, Peter (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2023)
This article presents a comparative study of two series of mathematics textbooks for lower secondary schools from Slovakia and the Czech Republic. The analysis focuses on the presence of reasoning and proving (R&P) solved tasks in geometry. Different ways of reasoning are analysed as well. The data were analysed using descriptive statistics methods. Results show similarities in the ways of reasoning present in both textbook series. Nevertheless, there are very different numbers of solved tasks and solved tasks focusing on R&P. This might be caused by different approaches textbook authors took with involving pupils in tasks with instructions. Although the deductive way of reasoning prevails in both countries, other ways are also present. The majority of solved R&P tasks also provide insight and explanation of geometrical statements.